Analysis of The Effect of Soundproofing on Ship Engines Based on Composite Materials Made from Tofu Dregs (Glycine Max L Merill) - Aurista Miftahatul Ilmah; Anauta Lungiding Angga Risdianto; Belgis Risky Wijaya; Arief Syarifuddin; Triyanti Irmiyana; Taufan Prasetyo; Muhammad Arus Samudera; Mohammad Hamid (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
Minimizing ship noise and vibrations is crucial due toÂ  potentially severe consequences, such as communication problems, sleep disturbances, stress, and structural damage. To address this, effective dampers are necessary. Many soundproofing materials now utilize natural fiber waste to replace synthetic materials, which are harmful to environment. One underutilized natural fiber is tofu dregs, which contain fibers suitable for sound absorption. This study investigates using tofu dregs as a composite material in sound-dampening applications. Composites are materials engineered from two or more substances with different properties to create a heterogeneous mixture. In this research, sound-dampening composites were developed using tofu dregs combined with carbon black and talc duco. The study found that the composite containing 60 grams of tofu dregs, 60 grams of talc duco, and 50 grams of resin achieved a sound absorption coefficient of Î± = 0.19. Meanwhile, the composite with 60 grams of tofu dregs, 50 grams of carbon black, and 50 grams of resin achieved a higher sound absorption coefficient of Î± = 0.24. These results indicate that the tofu dregs and carbon black composite offer superior sound absorption compared to tofu dregs and talc duco composite, demonstrating potential of tofu dregs as an eco-friendly soundproofing material.